Aplicação de filtro harmônico em sistemas elétricos de baixa tensão utilizando Lógica Fuzzy - CIRINO, Weverson dos Santos (Universidade Federal do Pará, 2011)
In an electric system several circuits and industrial equipments that behave as no-lineal devices exist. That behavior generates distortions in the electric system. Those distortions are called of Harmonic. This article introduces one of the several solutions to minimize that problem through the use of passive harmonic filters. The application of that filter will feel through a tool of computer generated to analyze and to detect which harmonic are present in the entrance sign and they harm the quality of the supply service, as well as, in projecting the passive filter. The Algorithm is divided in two phases, one for analysis and detection and the other based on Fuzzy Logic for the definition of the state of the supply service - QEE (Quality of the Electric power).